Magneto-optisko rezonanšu signālu īpatnību izpēte sārmu metālu tvaikos - Kalvāns, Linards (Latvijas Universitāte, 2011)
Abstract The main subject of this thesis is theoretical modeling of bright and dark magneto-optical resonances observable on the D1 spectral line of alkali metals. A theoretical model based on the rate equations for Zeeman coherences is em- ployed in the research. The theoretical model was developed from the optical Bloch equations, applying the rotating wave approximation and the decorrela- tion approach to stochastic dierential equations. In this thesis the theoretical model is adapted to describe magneto-optical resonances observed in alkali metal vapor that is conned in either an ordinary cm-sized cell or an extremely thin cell, whose thickness is comparable to the ex- citation wavelength. A method for estimating the parameters of the theoretical model for either of the experimental conditions is developed in the paper. The adapted theoretical model is tested by comparing its results to the ex- perimentally registered data. The experimental results are obtained by exciting atoms with laser radiation and observing the dependence of the uorescence sig- nal on a magnetic eld. Atomic vapor of 85Rb, 87Rb, and Cs is used. Rubidium atoms are studied in both types of cells, but Cesium atoms only in ordinary cells. Altogether the results of the theoretical model describe the experimental results well. Aside from describing experiments, the theoretical model is employed as an independent tool to study the saturation of the contrast of the dark magneto- optical resonances and the formation of the dark states.
Investigation of the characteristics of magneto-optical resonances in alkali metal vapor
Elektroniskā versija nesatur pielikumus
Keywords: Fizika, astronomija un mehānika; Fizika; Fizika, materiālzinātne, matemātika un statistika